Evaluating the short-term cost-effectiveness of liraglutide versus lixisenatide in patients with type 2 diabetes in the United States. (2nd November 2017) - Hunt, B.; McConnachie, C.C.; Gamble, C.; Dang-Tan, T.
Abstract: Aims: Bringing patients with type 2 diabetes to recommended glycated hemoglobin (HbA1c) treatment targets can reduce the risk of developing diabetes-related complications. The aim of the present analysis was to evaluate the short-term cost-effectiveness of once-daily liraglutide 1.8 mg vs once-daily lixisenatide 20 μg as an add-on to metformin for treatment of type 2 diabetes in the US by assessing the cost per patient achieving HbA1c-focused and composite treatment targets. Materials and methods: Percentages of patients achieving recommended targets were obtained from the LIRA-LIXI trial, which compared the efficacy and safety of once-daily liraglutide 1.8 mg and once-daily lixisenatide 20 μg as an add-on to metformin in patients with type 2 diabetes failing to achieve glycemic control with metformin. Annual costs were estimated from a healthcare payer perspective. An economic model was developed to evaluate the annual cost per patient achieving target (cost of control) with liraglutide 1.8 mg vs lixisenatide 20 μg for five end-points. Results: Annual treatment costs were higher with liraglutide 1.8 mg than lixisenatide 20 μg, but this was offset by greater clinical efficacy, and the cost of control was lower with liraglutide 1.8 mg than lixisenatide 20 μg for all five end-points. The annual cost of control was USD 3, 850, USD 11, 404, USD 3, 807, USD 4, 299, and USD 6, 901 lower for liraglutide 1.8 mg than lixisenatide 20 μg for targets of HbA1c < 7.0%, HbA1c ≤ 6.5%, HbA1c < 7.0% and no weight gain, HbA1c < 7.0% with no weight gain and no confirmed hypoglycemia, and HbA1c < 7.0% with no weight gain and systolic blood pressure <140 mmHg, respectively. Conclusions: Once-daily liraglutide 1.8 mg was associated with greater clinical efficacy than once-daily lixisenatide 20 μg, which resulted in a lower annual cost of control for HbA1c-focused and composite treatment targets.